2010
DOI: 10.1016/j.jocd.2010.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Bone Quality: A Noninvasive Measure of Bone's Biomechanical Property in Osteoporosis

Abstract: We describe a novel approach to non-invasively characterize bone quality, a measurement that quantitates aggregate shock absorption capacity of load-bearing bones as a measure of mechanical structural integrity during exposure to real-time self-induced in-vivo loading associated with heel strike. The outcome measure, damping factor, was estimated at five load bearing anatomical sites: ankle, tibial tuberosity, femoral condyle, lower back (at 3 rd lumbar vertebra) and upper back (7th thoracic vertebra) plus the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 37 publications
1
12
2
Order By: Relevance
“…The current experiments differ from this work, since we used a frequency range of 0.5 to 20 Hz. This lower frequency range is consistent with previously performed mouse loading studies, in addition to results from clinical data that demonstrated importance of the phase shift angle in this range [2]. …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The current experiments differ from this work, since we used a frequency range of 0.5 to 20 Hz. This lower frequency range is consistent with previously performed mouse loading studies, in addition to results from clinical data that demonstrated importance of the phase shift angle in this range [2]. …”
Section: Discussionsupporting
confidence: 91%
“…Damping is the potential of the whole musculoskeletal system to effectively dissipate energy associated with loading. A recent set of clinical data indicates that postmenopausal women with vertebral fractures have low damping capacity at a number of different skeletal sites [2]. This intriguing observation suggests a potential, non-invasive diagnostic tool for evaluating susceptibility of bone fracture.…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have shown significant correlation between grip strength, biomechanical property and BMD [19,20], there was no significant correlation among these markers in the current study.…”
Section: Discussioncontrasting
confidence: 85%
“…Well‐designed large studies are needed to find precise beneficial doses in vivo and in clinical trials. Although some studies have shown significant correlation between grip strength, biomechanical property and BMD (Bhattacharya et al ., ; Di Monaco et al ., ), there was no significant correlation among these markers in this study. The application of Cimicifuga species for osteoporotic bone changes is continually discussed.…”
Section: Resultsmentioning
confidence: 98%